2022
DOI: 10.3390/polym14235054
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Transition in Non-Hydrogen-Bonded Polymers and Theory of Latent Decomposition

Abstract: Although thermosets and various biopolymers cannot be softened without being decomposed, the vast majority of thermoplastics are believed to exhibit thermal transitions solely related to physical alterations of their structure—a behavior typical of low molecular weight substances. In this study, Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR) and Thermogravimetry (TGA) were used to study the softening of four common non-hydrogen-bonded thermoplastic polymers (polypropyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Quercetin and gallic acid were also found to depress the thermochemical transition temperature of CA membranes [18]. Other polymers, such as poly(vinyl chloride) and polypropylene-graft-maleic anhydride were reported to exhibit thermochemical transition [19]. According to literature, similar peculiarities have also been reported for other substances, e.g., for lithium potassium tartrate monohydrate [20], flavonoids (quercetin dihydrate and rutin dihydrate) [21], and potassium perchlorate [22].…”
Section: Introductionmentioning
confidence: 52%
“…Quercetin and gallic acid were also found to depress the thermochemical transition temperature of CA membranes [18]. Other polymers, such as poly(vinyl chloride) and polypropylene-graft-maleic anhydride were reported to exhibit thermochemical transition [19]. According to literature, similar peculiarities have also been reported for other substances, e.g., for lithium potassium tartrate monohydrate [20], flavonoids (quercetin dihydrate and rutin dihydrate) [21], and potassium perchlorate [22].…”
Section: Introductionmentioning
confidence: 52%
“…Additionally, the mass loss at the first degradation step is significant and shifts the DSC signal in the exothermic direction. Hence, the first signal observed on the DSC curve is exothermic as a result of various reactions occurring simultaneously [ 38 ], but it should be noted that the decomposition is initially endothermic. To confirm the mechanism of copolymer decomposition, FTIR analysis of the emitted volatile degradation products was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, combined with TGA and DSC curves, it was found that when the temperature reached the softening temperature of PI and PI-SiCw, the nanocomposites had a certain amount of mass loss, which may be due to the fact that latent decomposition reached a maximum at the softening point [ 37 ]. This also explained the phenomenon of mass loss in PI-SiCw in the TGA curve before reaching a temperature of 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the residual weight of PI-SiCw nanocomposites was larger than that of the matrix, which increased from 44% to 49%. Moreover, the mass loss rate of PI-SiCw nanocomposites was fast around 65 • C and 450 • C. In the process of heating, the mass loss detected by TGA ranging from 50 • C to 100 • C may be due to the evaporation of water and some latent decomposition of polymer composites by heating [37]. The reaction process was divided into two stages.…”
Section: Tga and Dtg Analysismentioning
confidence: 99%